The concept of civil law incentives - Yu. I. Chalyi (Bulletin of Kharkiv National University of Internal Affairs)
Civil law incentives are characterised by both general legal and sectoral (specific) features. The dialectical combination of these features determines the civil law image of the category of “incentives”, which may be represented by the following provisions.